Reversible electrodeposition and stripping of magnesium from solvate ionic liquid–tetrabutylammonium chloride mixtures. Issue 69 (18th November 2020) - Geysens, Pieter; Fransaer, Jan; Binnemans, Koen
Abstract : Mixtures of magnesium-containing solvate ionic liquids and tetra- n -butylammonium chloride have low volatility and can be used as innovative electrolytes for reversible deposition of magnesium metal at high current density. Abstract : The physicochemical properties of three new magnesium-containing solvate ionic liquids are reported. The solvation structures were analysed by Raman spectroscopy, revealing a solvent separated ion pair structure at room temperature. The reversible electrodeposition and stripping of magnesium from mixtures of these solvate ionic liquids and tetra- n -butylammonium chloride is described. The electrolytes are significantly less volatile than similar dilute electrolytes, even at elevated temperatures and the deposition current densities exceed 1 A dm −2 at 80 °C. The influence of the chloride concentration on magnesium deposition was studied with cyclic voltammetry and chronopotentiometry. It was found that the stripping of magnesium is governed by two competing reactions, and the addition of tetrabutylammonium chloride to the solvate ionic liquids was necessary to prevent passivation and efficiently strip the deposited magnesium.